Animal influenza virus infections in humans: A commentary. (November 2019) - Borkenhagen, Laura K.; Salman, Mo D.; Ma, Mai-Juan; Gray, Gregory C.
Highlights: Influenza A viruses (IAVs) that are enzootic in animals often have potential to infect humans, however this risk is not equal for all viruses. In this report we briefly review the risk of human infections from swine, avian, feline, equine, and canine IAVs. We conclude that given equal animal exposures, humans are most likely to be infected with swine influenza IAVs. Worldwide, the variety of IAVs in swine farms is increasing and surveillance for IAVs with pandemic potential is woefully neglected. New One Health collaborations with swine industries must be brokered to help mitigate these growing pandemic risks. Abstract: Here we review evidence for influenza A viruses (IAVs) moving from swine, avian, feline, equine, and canine species to infect humans. We review case reports, sero-epidemiological, archeo-epidemiological, environmental, and historical studies and consider trends in livestock farming. Although this focused review is not systematic, the aggregated data point to industrialized swine farming as the most likely source of future pandemic viruses, yet IAV surveillance on such farms is remarkably sparse. We recommend increased biosafety and biosecurity training for farm administrators and swine workers with One Health-oriented virus surveillance throughout industrialized farming and meat production lines. Collaborative partnerships with human medical researchers could aid in efforts to mitigate emerging virus threats by offering new surveillance and diagnostic technologies to livestock farming industries.